PENCEGAHAN PUTUS SEKOLAH PAUD DENGAN MELIBATKAN ORANG TUA - Saffanatun Hasna; RR. Deni Widjayatri (QURROTI, 2022)
This paper is purposed to find out the role of parents to overcome the problem of dropping out of school in children and how parents deal with the problems. this research using descriptive qualitative methods based on literature review. The family is the first place for children to get education. Parents are the first and main role for children's education to support growth and development that determines their future. parents also have an important role to prevent, control, and coaching. Based on the reading results obtained, it can be concluded that the way parents deal with the problem of dropping out of school in children is establish a good communication and also invite children to discuss in two directions, then provide a motivate so that children have a strong determination in carrying out their education to a higher level.